anonymous
  • anonymous
Solve the system (using substitution) x - 2y = -7 and 3x + 4y = -6. The y-value of the solution is:
Mathematics
At vero eos et accusamus et iusto odio dignissimos ducimus qui blanditiis praesentium voluptatum deleniti atque corrupti quos dolores et quas molestias excepturi sint occaecati cupiditate non provident, similique sunt in culpa qui officia deserunt mollitia animi, id est laborum et dolorum fuga. Et harum quidem rerum facilis est et expedita distinctio. Nam libero tempore, cum soluta nobis est eligendi optio cumque nihil impedit quo minus id quod maxime placeat facere possimus, omnis voluptas assumenda est, omnis dolor repellendus. Itaque earum rerum hic tenetur a sapiente delectus, ut aut reiciendis voluptatibus maiores alias consequatur aut perferendis doloribus asperiores repellat.

Get our expert's

answer on brainly

SEE EXPERT ANSWER

Get your free account and access expert answers to this
and thousands of other questions.

anonymous
  • anonymous
Solve the system (using substitution) x - 2y = -7 and 3x + 4y = -6. The y-value of the solution is:
Mathematics
schrodinger
  • schrodinger
See more answers at brainly.com
At vero eos et accusamus et iusto odio dignissimos ducimus qui blanditiis praesentium voluptatum deleniti atque corrupti quos dolores et quas molestias excepturi sint occaecati cupiditate non provident, similique sunt in culpa qui officia deserunt mollitia animi, id est laborum et dolorum fuga. Et harum quidem rerum facilis est et expedita distinctio. Nam libero tempore, cum soluta nobis est eligendi optio cumque nihil impedit quo minus id quod maxime placeat facere possimus, omnis voluptas assumenda est, omnis dolor repellendus. Itaque earum rerum hic tenetur a sapiente delectus, ut aut reiciendis voluptatibus maiores alias consequatur aut perferendis doloribus asperiores repellat.

Get this expert

answer on brainly

SEE EXPERT ANSWER

Get your free account and access expert answers to this
and thousands of other questions

amistre64
  • amistre64
when solving by substitution we want to get a value for one variable in "terms" of the other. x-2y = -7 x = -7 +2y well use this for our value of "x" in the other equation. 3x +4y = -6 3(-7 +2y) + 4y = -6 -21 +6y +4y = -6 10y = -6+21 10y = 15 y = 15/10 = 1.5 the value of y should be 1.5 if I kept my wits about me :) better double check myself tho..
amistre64
  • amistre64
x = -7 +2(1.5) x = -7 + 3 x=-4 -4 - 2(1.5) = -7 -4 -3 = -7 ..good there 3x + 4y = -6 3(-4) + 4(1.5) = -6 -12 +6 = -6 -6 = -6 ....its all good :)
amistre64
  • amistre64
Does that make sense to you?

Looking for something else?

Not the answer you are looking for? Search for more explanations.

More answers

anonymous
  • anonymous
Yes. That helped a lot. Thank you

Looking for something else?

Not the answer you are looking for? Search for more explanations.